Global burden of cardiovascular disease due to low physical activity, 1990–2021 - Nan Wu; Jian Wang; Yingchu Hu; Tingsha Du; Peng Shu; Caijie Shen; Xiaomin Chen (Scientific Reports)
Abstract We aimed to clarify the distribution of the spatiotemporal burden of Low physical activity (LPA)-related cardiovascular disease (CVD) at the global, regional, and national levels from 1990 to 2021. We systematically extracted Global Burden of Disease Study (GBD) 2021 data on CVD burden attributable to LPA from 1990 to 2021, stratified by Socio-demographic Index (SDI) quintiles and 21 GBD geographical regions. Three complementary metrics were employed: (1) Age-standardized death rate (ASDR) and (2) Disability-Adjusted Life Year (DALY) rate provided cross-sectional burden estimates, while (3) Estimated Annual Percentage Change (EAPC) quantified temporal trends in ASDR/DALY rates. The EAPC-derived trend patterns were further analyzed in conjunction with SDI levels and regional variations to identify disparities in physical inactivity-related CVD burden. The age-standardized DALY rate (EAPC = -1.30) and ASDR (EAPC = -1.41) for CVD attributable to LPA showed a decreasing trend from 1990 to 2021. The highest age-standardized DALY rate and ASDR per 100,000 population across all five SDI regions were observed in the Low-middle SDI region (111.53; 5.67). Among the 21 geographic regions and 204 countries, the highest age-standardized DALY rate and ASDR per 100,000 population for CVD attributable to LPA in 2021 were both reported in North Africa and the Middle East (211.62; 10.50), with Sudan having the highest rates (616.58; 24.56). The largest increase in the age-standardized DALY rate from 1990 to 2021 was observed in Southeast Asia (EAPC = 0.19), while the most substantial increase in ASDR was noted in Southern sub-Saharan Africa (EAPC = 0.44). Both the age- standardized DALY rate and ASDR increased the most in Lesotho (EAPC = 2.30; EAPC = 2.39). Although the global burden of CVD attributable to LPA has decreased from 1990 to 2021, the burden remains significant in low- and middle-income countries.